Reducing arsenic toxicity using the interfacial oxygen nanobubble technology for sediment remediation - Tang, Ying; Zhang, Meiyi; Zhang, Jing; Lyu, Tao; Cooper, Mick; Pan, Gang (Elsevier, 2021)
The arsenic (As)-bearing eutrophic waters may suffer from the dual conditions of harmful algal blooms and release of As, driven by algal-induced hypoxia/anoxia. Here, we investigate the use of interfacial oxygen (O2) nanobubble technology to combat the hypoxia and control As exposure in simulated mesocosm experiments. It was observed that remediation of algal-induced hypoxia at the sediment-water interfaces (SWI) by application of O2 nanobubbles reduced the level of dissolved As from 23.2 μg L−1 to <10 μg L−1 and stimulated the conversion of As(III) to the less toxic As(V) (65–75%) and methylated As (10–15%) species. More than half of the oxidation and all the methylation of As(III) resulted from the manipulation by O2 nanobubbles of microbes responsible for As(III) oxidation and methylation. Hydroxyl radicals were generated during the oxidation of reductive substances at the SWI in darkness, and should be dominant contributors to As(III) abiotic oxidation. X-ray absorption near-edge structure (XANES) spectroscopic analysis demonstrated that surface sediments changed from being sources to acting as sinks of As, due to the formation of Fe-(hydr)oxide. Overall, this study suggests that interfacial O2 nanobubble technology could be a potential method for remediation of sediment As pollution through the manipulation of O2-related microbial and geochemical reactions
Keywords: Hydroxyl radicals; Arsenic metabolism functional genes; Hypoxia remediation; Nanobubble; Arsenic oxidation; Eutrophic waters